'We All Want Some Figgy Pudding' - Atkins, Anne (Petits Propos Culinaires, 2024)
Christmas fare is traditional, but the traditions have been and still are subject to change. The title of this article (taken from the Christmas carol 'We wish you a Merry Christmas') may mystify people who are only familiar with contemporary Christmas puddings. It would be natural, reflecting on this, to suppose that things like Christmas pudding and mince pies have been steadily departing further and further away from their mediaeval prototypes. So they have, on the whole. But present ideas about, for example, the undesirability of consuming sugar may be reversing the trend in certain aspects. Anne Atkins has been experimenting on these lines and here presents the resulting recipes.